Alpha‐1‐antitrypsin reduces inflammation and exerts chondroprotection in arthritis. Issue 5 (31st March 2021) - Kaneva, Magdalena K.; Muley, Milind M.; Krustev, Eugene; Reid, Allison R.; Souza, Patricia R.; Dell'Accio, Francesco; McDougall, Jason J.; Perretti, Mauro
Abstract: While new treatments have been developed to control joint disease in rheumatoid arthritis, they are partially effective and do not promote structural repair of cartilage. Following an initial identification of α‐1‐Antitrypsin (AAT) during the resolution phase of acute inflammation, we report here the properties of this protein in the context of cartilage protection, joint inflammation, and associated pain behavior. Intra‐articular and systemic administration of AAT reversed joint inflammation, nociception, and cartilage degradation in the KBxN serum and neutrophil elastase models of arthritis. Ex vivo analyses of arthritic joints revealed that AAT promoted transcription of col2a1, acan, and sox9 and downregulated mmp13 and adamts5 gene expression. In vitro studies using human chondrocytes revealed that SERPINA1 transfection and rAAT protein promoted chondrogenic differentiation through activation of PKA‐dependent CREB signaling and inhibition of Wnt/β‐catenin pathways. Thus, AAT is endowed with anti‐inflammatory, analgesic, and chondroprotective properties that are partially inter‐related. We propose that AAT could be developed for new therapeutic strategies to reduce arthritic pain and repair damaged cartilage.